Changing trends of cesarean section using Robson’s Ten-group classification in tertiary centre: a retrospective study - Singh, Anamika; ., Sadiqunnisa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of this study was to investigate and compare the CS rates at a tertiary care medical college setting centre which has a high referral rate of complicated pregnancies and make analysis based on the 10-group classification. Methods: This is a retrospective study carried out department obstetrics and gynecology of a tertiary care medical college hospital in Mangalore and includes all deliveries over a period of five years from Jan 14 to Dec 2018 and it was compared with the c-section from January 2007 to December 2011. Results: The overall CS (cesarean section) during the period 2014-18 was 31.85 which were significantly greater then 2007-11 period (20.59%). The main contributing groups to the overall CS rate were the previous CS (Group 5) and Primigravida groups, (Groups 1 and 2) 80%. Conclusions: It is important that efforts to reduce the overall CS rate should focus on reducing the primary CS rate. The application of Robson’s Ten-group classification (TGCS) in centre has helped to identify the main groups of subjects who had the overall maximum CSR.